Espaço aéreo superior de pacientes submetidos à cirurgia de avanço maxilo-mandibular: qual a estabilidade do ganho após 5 anos? - Araújo, Phelype Maia (2017)
Current literature has argued that maxillo-mandibular advancement obtained in orthognathic surgery promotes improvement in air space, thus it is a therapeutic acceptable option for those patients which present dento-skeletal deformities. Providing an aesthetic and functional result, so many implications reflect in this surgical treatment, with that mutiples facial changes impact on personal and social life, bringing benefits to peolpe life quality. Objective: The objective of this study is to compare the relative changes in three specific - regions, nasopharynx, oropharynx and hypopharynx - to the total area, to the volume and to the most constricted area of the airways after maxillo-mandibular advancement surgery, using cone-bean computed tomography (CBCT) in a period of up to 5 years. Material and Methods: A retrospective study in which four CT scans of each patient from a total sample of 30 patients (men and women) with maxillo-mandibular deficiency who had been submitted to orthognathic surgery with bimaxillary advancement were evaluated in a pre-operative (T0), immediate postoperative period of up to 30 days after surgery (T1), late postoperative period, 1 year after surgery (T2), and late postoperative period, 3 to 5 years after surgery (T3). From this, it was performed the quantification of the total area, volume and area of greatest constriction of the airways at the three points, nasopharynx, oropharynx and hypopharynx was and compared between them. Results: It was found a mean gain of total area of T0 in relation to T1 of 6.41cm2 (86.97%), T0 in relation to T2 of 3.04cm2 (41.70%), T0 in relation To T3 of 1.67cm2 (23.07%). When the airway was divided by regions, an area gain was observed in the nasopharynx of T0 in relation to T1 of 3.30cm2 (91.20%), T0 in relation to T2 of 1.29cm2 (37.23%), T0 to T3 of 0.63cm2 (20.50%). In the oropharynx region, a T0 gain was observed in relation to T1 of 1.39cm2 (71.27%), T0 in relation to T2 of 0.60cm2 (30.70%), T0 in relation to T3 of 0.30cm2 (18.8%) and in the hypopharynx region a T0 gain was observed in relation to T1 of 1.37cm2 (107.13%), T0 in relation to T2 of 0.70cm2 (55.13% ), T0 to T3 of 0.34cm2 (28.43%). When the total volume gain of T0 was evaluated in relation to T1 of 137.18 cm3 (81.83%), T0 in relation to T2 of 66.59cm3 (39.07%), T0 in relation to T3 of 32 , 92cm3 (20.97%) and when the airway was divided by regions, there was a volume gain in the nasopharynx of T0 in relation to 12 T1 of 81.97cm3 (90.57%), T0 in relation to T2 Of 40.99cm3 (45.70%), from T0 to T3 of 16.87cm3 (19.86%). In the oropharynx region, there was a gain of T0 in relation to T1 of 37.37 cm3 (87.73%), T0 in relation to T2 of 21.01 cm3 (50.43%), T0 in relation to T3 Of 11.94 cm3 (21.73%) and in the hypopharyngeal region, a gain of T0 was observed in relation to T1 of 55.79 cm3 (136.50%), from T0 to T2 of 22.81 cm3 (96 , 90%), from T0 to T3 of 13.68cm3 (20.92%). Finally, the most constricted airway area gain was measured by regions, in the nasopharynx of T0 in relation to T1 of 1.85cm2 (308.10%), T0 in relation to T2 of 1.32cm2 (221, 90%), from T0 to T3 of 0.59cm2 (93.57%). In the oropharyngeal region, a gain was observed of T0 in relation to T1 of 0.88cm2 (147.87%), T0 in relation to T2 of 0.48cm2 (83.80%), T0 in relation to T3 of 0.35 cm 2 (46.30%) and in the hypopharynx region, a T0 gain was observed in relation to T1 of 1.31 cm2 (178.27%), T0 in relation to T2 of 0.68 cm2 (92.95 %), From T0 to T3 of 0.36cm2 (50.63%). Conclusion: Finally, it was concluded that maxillo-mandibular advancement is a surgical technique that provides a gain in area, volume and most constricted area of the upper upper airways in the immediate, late postoperative period of 1 year and late postoperative period of 3 to 5 years, showing, however, a partial loss in late periods.